PRODUKTIVITAS KERJA DITINJAU DARI KONFLIK PADA KARYAWAN UNIVERSITAS TJUT NYAK DHIEN MEDAN - Sely Ema Saputri; Karlina Yunisa (Yana Research, 2021)
Penelitian ini bertujuan untuk mengetahui: (1) hubungan self regulated learning dengan prokrastinasi akademik mahasiswa; (2) hubungan self efficacy dengan prokrastinasi akademik mahasiswa; (3) hubungan antara self regulated learning dan self efficacy dengan prokrastinasi akademik mahasiswa. Hipotesis yang diajukan adalah hubungan negatif antara self regulated learning dan self efficacy dengan prokrastinasi akademik mahasiswa, dengan asumsi semakin tinggi self regulated learning dan self efficacy, maka semakin rendah prokrastinasi akademik mahasiswa. Sebaliknya semakin rendah self regulated learning dan self efficacy maka semakin tinggi prokrastinasi akademik mahasiswa. Jumlah sampel berjumlah 61 orang. Teknik pengambilan sampel menggunakan teknik sampel jenuh. Teknik pengumpulan data menggunakan angket. Metode penelitian yang digunakan adalah metode kuantitatif. Hasil penelitian menyimpulkan bahwa: (1) terdapat hubungan negatif antara self regulated learning dengan prokrastinasi akademik mahasiswa; (2) terdapat hubungan negatif antara self efficacy dengan prokrastinasi akademik mahasiswa; (3) terdapat hubungan negatif antara self regulated learning dan self efficacy dengan prokrastinasi akademik mahasiswa Kata Kunci: Self Regulated Learning, Self Efficacy, Prokrastinasi Akademik Abstract This study aims to determine: (1) the relationship between self regulated learning and student academic procrastination; (2) the relationship of self efficacy with student academic procrastination; (3) the relationship between self regulated learning and self efficacy with student academic procrastination. The hypothesis proposed is a negative relationship between self regulated learning and self efficacy with student academic procrastination, assuming the higher self regulated learning and self efficacy, the lower the student academic procrastination. Conversely, the lower the self regulated learning and self efficacy, the higher the student's academic procrastination. The number of samples is 61 people. The sampling technique uses saturated sample techniques. The data collection techniq uses questionnaire. The research method used is quantitative methods. The results of the study conclude that: (1) there is a negative relationship between self regulated learning and student academic procrastination; (2) there is a negative relationship between self efficacy and student academic procrastination; (3) there is a negative relationship between self regulated learning and self efficacy with student academic procrastination. Keywords: Self Regulated Learning, Self Efficacy, Academic Procrastination